#### Answer

$(g \circ f)(x) = x-7$

#### Work Step by Step

If $f(x) = x \ , \ g(x) = x-7$ and $h(x) = x^2-6x+5$
$(g \circ f)(x) = g(f(x)) = x-7$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$(g \circ f)(x) = x-7$

If $f(x) = x \ , \ g(x) = x-7$ and $h(x) = x^2-6x+5$
$(g \circ f)(x) = g(f(x)) = x-7$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.